Evaluation of the Implementation of Guidance and Counseling Programs (A Literature Study) - M Nu'man Al Hadziq; Aprilia Sari Yudha (Demagogi: Journal of Social Sciences, Economics and Education, 2024)
This study aims to explain in detail the theoretical basis and implementation of the evaluation of guidance and counseling programs in schools. The research method used is literature study, with data collection using the documentation method. Data analysis was performed using content analysis method. To ensure research accuracy and prevent misinformation in data analysis, relevant references were checked and re-read. The main objective of this research is to develop the theoretical basis and implementation of the guidance and counseling program. The results of this study include the elaboration of the basic theory and implementation of the guidance and counseling program as a whole, which includes: 1) understanding of program evaluation, 2) components of the guidance and counseling program, 3) understanding of evaluation of guidance and counseling programs, 4) the benefits of carrying out evaluation of guidance and counseling programs counseling, 5) evaluation procedures for guidance and counseling programs, 6) barriers to evaluating guidance and counseling programs.